The spleen and sickle cell disease: the sick(led) spleen. (26th May 2014) - Brousse, Valentine; Buffet, Pierre; Rees, David
Summary: The spleen has a combined function of immune defence and quality control of senescent or altered red cells. It is the first organ injured in sickle cell anaemia (SCA) with evidence of hyposplenism present before 12 months in the majority of children. Repeated splenic vaso‐occlusion leads to fibrosis and progressive atrophy of the organ (autosplenectomy), which is generally complete by 5 years in SCA. The precise sequence of pathogenic events leading to hyposplenism is unknown. Splenic injury is generally silent and progressive. It can be clinically overt with acute splenic sequestration of red cells, an unpredictable and life‐threatening complication in infants. Splenomegaly, with or without hypersplenism, can also occur and can coexist with loss of function. Hyposplenism increases the susceptibility of SCA children to infection with encapsulated bacteria, which is notably reduced by penicillin prophylaxis and immunization. Whether hyposplenism indirectly increases the risk of vaso‐occlusion or other circulatory complications remains to be determined.